Assessment of the Major Anti-Tuberculosis Drugs Available to Patients at Primary Health Care Centers in Baghdad City - okab, ammar; ali, eqbal (Iraqi National Journal of Nursing Specialties, 2017)
Objective: To assess the major anti-tuberculosis drugs available to patients at primary health care centers in Baghdad city. Methodology: A descriptive cross-sectional study design is carried out in order to achieve the objectives of the study by using the assessment technique in primary health care centers from December 29th, 2014 to July 10 th, 2015. probability sampling is select based on the study design. Eighteen primary health care centers are select according to criteria of sample to the study and for the purpose of the study, is select (6) sectors and (11) Primary Health Care Centers (PHCC) from Baghdad Health Department/Al-Rusafa Directorate and (6) sectors and (7) primary health care centers from Baghdad Health Department/Al- Karkh Directorate in Baghdad city. The data is collect by special questionnaire to obtained general information about primary health care centers (county, Sector, named of primary health care centers, estimated number of population and the number of patients use Tuberculosis drugs available in primary health care centers. Data analysis is done by using program of (SPSS) version 20 , Descriptive data through determination of: Frequencies , Percentages and, Inferential statistical data analysis is done applying Chi –square test for determining the association between the study main domains. Results: 22% of drugs KIT (HRZE)and KIT (HR) and present highly significant association between number of patients use Tuberculosis drugs and preventive drug (Izenazahid) . . Recommendations: based on the study’s findings, it is highly recommends that the Ministry of Health maintains providing the anti-tuberculosis medications on a regular basis.